Patients’ Perceptions of the Effectiveness of Counseling Therapy: A Qualitative Study in Mental Health Services - Wahyuni, Nur (Journal of Therapia, 2025)
The evaluation of counseling therapy effectiveness in mental health services has traditionally relied on clinically defined and professionally driven outcome indicators, often marginalizing patients’ subjective experiences. This study aims to explore how patients perceive and construct the effectiveness of counseling therapy, identify relational and contextual factors shaping these perceptions, and analyze their implications for therapeutic continuity. Using a qualitative approach with an interpretative phenomenological design, data were collected through in-depth semi-structured interviews with patients who had undergone at least three counseling sessions in mental health service settings. The data were analyzed thematically through iterative coding and interpretative processes. The findings reveal that patients conceptualize therapeutic effectiveness as a multidimensional and dynamic experience encompassing emotional validation, enhanced self-understanding, relational trust, and contextual relevance, rather than symptom reduction alone. The quality of the therapeutic relationship and service context emerged as central determinants shaping patients’ perceptions. Positive perceptions were found to foster sustained engagement and real-life application of therapeutic insights, whereas negative perceptions contributed to therapy dropout despite clinical improvement. The study concludes that integrating patients’ subjective perspectives into the evaluation of counseling therapy is essential for improving service quality, therapeutic continuity, and patient-centered mental health care.